The Golgi apparatus regulates cGMP-dependent protein kinase I compartmentation and proteolysis - Kato, Shin (Am J Physiol Cell Physiol, 2015)
cGMP-dependent protein kinase I (PKGI) is an important effector of cGMP signaling that regulates vascular smooth muscle cell (SMC) phenotype and proliferation. PKGI has been detected in the perinuclear region of cells, and recent data indicate that proprotein convertases (PCs) typically resident in the Golgi apparatus (GA) can stimulate PKGI proteolysis and generate a kinase fragment that localizes to the nucleus and regulates gene expression. However, the role of the endomembrane system in PKGI compartmentation and processing is unknown. Here, we demonstrate that PKGI colocalizes with endoplasmic reticulum (ER), ER-Golgi intermediate compartment, GA cisterna, and trans-Golgi network proteins in pulmonary artery SMC and cell lines. Moreover, PKGI localizes with furin, a trans-Golgi network-resident PC known to cleave PKGI. ER protein transport influences PKGI localization because overexpression of a constitutively inactive Sar1 transgene caused PKGI retention in the ER. Additionally, PKGI appears to reside within the GA because PKGI immunoreactivity was determined to be resistant to cytosolic proteinase K treatment in live cells. The GA appears to play a role in PKGI proteolysis because overexpression of inositol 1,4,5-trisphosphate receptor-associated cGMP kinase substrate, not only tethered heterologous PKGI-β to the ER and decreased its localization to the GA, but also diminished PKGI proteolysis and nuclear translocation. Also, inhibiting intra-GA protein transport with monensin was observed to decrease PKGI cleavage. These studies detail a role for the endomembrane system in regulating PKGI compartmentation and proteolysis. Moreover, they support the investigation of mechanisms regulating PKGI-dependent nuclear cGMP signaling in the pulmonary vasculature with Golgi dysfunction.